A Comparison of CT Manifestations Between Coronavirus Disease 2019 (COVID-19) and Other Types of Viral Pneumonia - Mao, Haixia; Li, Xiaoshan; Lin, Xiaoming; Zhou, Lijuan; Zhang, Xiuping; Cao, Yang; Jiang, Yilun; Chen, Hongwei; Fang, Xiangming; Gu, Lan (Current Medical Imaging, 2021)
Background: Though imaging manifestations of COVID-19 and other types of viral pneumonia are similar, their clinical treatment methods differ. Accurate, non-invasive diagnostic methods using CT imaging can help develop an optimal therapeutic regimen for both conditions. Objective: To compare the initial CT imaging features in COVID-19 with those in other types of viral pneumonia. Methods: Clinical and imaging data of 51 patients with COVID-19 and 69 with other types of viral pneumonia were retrospectively studied. All significant imaging features (Youden index >0.3) were included for constituting the combined criteria for COVID-19 diagnosis, composed of two or more imaging features with a parallel model. McNemar's chi-square test or Fisher's exact test was used to compare the validity indices (sensitivity and specificity) among various criteria. Results: Ground glass opacities (GGO) dominated density, peripheral distribution, unilateral lung, clear margin of lesion, rounded morphology, long axis parallel to the pleura, vascular thickening, and crazy-paving pattern were more common in COVID-19 (p <0.05). Consolidation-dominated density, both central and peripheral distributions, bilateral lung, indistinct margin of lesion, tree-inbud pattern, mediastinal or hilar lymphadenectasis, pleural effusion, and pleural thickening were more common in other types of viral pneumonia (p < 0.05). GGO-dominated density or long axis parallel to the pleura (with the highest sensitivity), and GGO-dominated density or long axis parallel to the pleura or vascular thickening (with the highest specificity) are well combined criteria of COVID-19. Conclusion: The initial CT imaging features are helpful for the differential diagnosis of COVID-19 and other types of viral pneumonia.
Keywords: Coronavirus disease 2019